Magnesium as a Neuroprotective Agent: A Review of Its Use in the Fetus, Term Infant with Neonatal Encephalopathy, and the Adult Stroke Patient - Lingam, Ingran; Robertson, Nicola J (Developmental neuroscience, 2018)
Magnesium is an intracellular cation essential for many en-zymatic processes and cellular functions. Magnesium sulfate acts as an endogenous calcium channel antagonist at neuronal synapses, thought to prevent excessive activation of N-methyl-D-aspartate receptors by excitatory amino acids, such as glutamate, and by downregulation of proinflammatory pathways. Early intervention is essential in the prevention of the secondary phase of neuronal injury. The immature brain is particularly prone to excitotoxicity, and inflammation has been strongly implicated in the pathogenesis of cerebral palsy. This article explores the current status of magnesium being used as an adjunct to hypothermia in term neonatal encephalopathy (NE) against a background of its use in other populations. There is some evidence for magnesium sulfate as a neuroprotective agent, however animal studies of NE at term equivalent age have been confounded by concomitant hypothermia induced by magnesium itself. Nevertheless, the combination of magnesium and cooling has been shown to be more effective than either treatment alone in adult rodents. In the preterm baby, magnesium sulfate given antenatally in threatened preterm labor has demonstrated a significant reduction in the risk of cerebral palsy at 2 years of age, though the benefit is not clear at school age. In adult clinical studies of ischemic and hemorrhagic stroke, there have been disappointing results for magnesium sulfate as a neuroprotective strategy. Importantly, clinical neurological scores may be affected by the increased hypotonia observed. We suggest that magnesium sulfate should be carefully re-evaluated as a neuroprotective agent given its favorable safety profile, relative low cost, and widespread availability.